Strengthening of timber beams with pretensioned CFRP strips. (December 2021) - Halicka, Anna; Ślósarz, Szymon
Abstract: The article presents the results of research on the strengthening of timber beams with the use of pretensioned CFRP strips. In the beginning, the review of literature regarding both passive and active strengthening methods of timber beams with steel bars, steel mats and FRP strips is presented. The review is followed by the description of a test program concerning the strengthening of solid timber beams with pre-tensioned composite strips. In four series of beams various levels of prestress were applied. The article discusses all stages of beams production, including the prestressing process. The behavior of beams over 28 days after prestressing is reported. The results of four-point bending of strengthened beams are described. The ultimate forces, mechanisms of failure as well as the "load–deflection" relationships in individual beam series were analyzed in comparison with the reference beams. The possibility of prestressing of solid timber beams and the reduction of their deflection due to prestress was proved.